Potential Implications of Problem Based Learning On Developing Learners' Exposition Text Writing Skills In Indonesian Language Classroom - wangi, Nisaul barokati seliro; Rofik, Abdur; Wahyudi, Eko Yusuf; Ubaidillah, Aan Fardani (Universitas Islam Raden Rahmat Malang, 2023)
Teacher creativity in teaching writing skills to learners’ in the classroom is very important. Because not all learners’ have the same ability in writing, especially writing Exposition texts which are notoriously difficult, narrative in nature, and require critical thinking skills. Therefore, in teaching teachers need to apply appropriate learning strategies that can facilitate students' learning needs and interests, one of which is using the Problem Based Learning (PBL) model. PBL is one of the well-known learning models that has potential implications in facilitating students' learning difficulties in writing. The purpose of this study was to investigate the improvement of lower grade students' exposition text writing skills using the PBL model. This research uses Classroom Action Research (CAR) which is qualitative in nature. The research subjects were lower grade (X) students of SMAS Sunan Drajat Sugio. The research instruments and data used were observation sheets, student questionnaires, and learning outcome tests. Data collection was carried out using observation sheets, response questionnaire sheets, and student learning test results. The technique used was descriptive qualitative data analysis technique. (1) The results of the observation of student activity increased from cycle I to cycle II. The increase was 45.16%. This indicates that student activity while using the PBL model is very effective, because in cycle II 96.77% of students were actively involved in learning. The results of observing student responses have increased from cycle I to cycle II. The increase was 29.04% which indicates that students' positive response to this learning is good (3) Student learning outcomes using the PBL model have increased, this can be seen from the initial condition value of students who are complete at 45.16%. Then in cycle I it became 64.51%. Increased in cycle II to 100%. Thus, the use of the PBL model has a major positive impact and is successful in an effort to improve students' activities, responses, and exposition text writing skills in the classroom.